Shopee Live as a Trigger of Consumptive Behavior: A Perspective on Character and Self-Control among Boarding Students - Zebua, Sovi septia diana; Laoli, Adieli; Tafona, Yunita Tafona; Ziliwu, Yurman; Zendrato, Junita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines how Shopee Live triggers consumptive behavior among boarding house students by focusing on the roles of character and self-control. Using a qualitative phenomenological approach, data were collected through interviews, observations, and documentation. The findings indicate that Shopee Live encourages impulsive buying through emotional engagement, interactive features, and promotional pressure. Students with strong self-control and positive character traits tend to make more rational purchasing decisions, while those with weaker self-regulation are more susceptible to unplanned purchases. In addition, peer influence in boarding environments strengthens consumptive tendencies. This study concludes that consumptive behavior in live streaming commerce is shaped by the interaction between digital stimuli and internal psychological factors, highlighting the importance of self-control and character awareness in promoting responsible online shopping behavior.